Creation of courses from unstructured materials in nature for children’s physical activit - Stanišić, Irena R.; Vlajković, Dejana (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2025)
The aim of this study is to create a course made of unstructured materials in nature for the physical activity of preschool children. A total of 62 children (32 girls and 30 boys) from the preschool program at the "Kolibri" PU "Radost" preschool institution in Vrnjačka Banja participated in this project. The process consisted of several phases: selecting a location for the course; acquiring unstructured materials for the activity; designing templates and planning the course layout; building the course; and opening the course, which included guiding the children through the unstructured material course and explaining the tasks; мonitoring included assessing the children’s interest in the course, and evaluation involved summarizing the results.